Smoking cessation in patients with respiratory diseases: a high priority, integral component of therapy - (:unkn) unknown (EUROPEAN RESPIRATORY SOC JOURNALS LTD, 2006)
Smoking cessation is the one of the most important ways to improve the prognosis of patients with respiratory disease. The Task Force on guidelines for smoking cessation in patients with respiratory diseases was convened to provide evidence-based recommendations on smoking cessation interventions in respiratory patients. Based on the currently available evidence and the consensus of an expert panel, the following key recommendations were made. 1) Patients with respiratory disease have a greater and more urgent need to stop smoking than the average smoker, so respiratory physicians must take a proactive and continuing role with all smokers in motivating them to stop and in providing treatment to aid smoking cessation. 2) Smoking cessation treatment should be integrated into the management of the patient's respiratory condition. 3) Therapies should include pharmacological treatment (i.e. nicotine replacement therapy, bupropion or varenicline) combined with behavioural support. 4) Respiratory physicians should receive training to ensure that they have the knowledge, attitudes and skills necessary to deliver these interventions or to refer to an appropriate specialist. 5) Although the cost of implementing these recommendations will partly be offset by a reduction in attendance for exacerbations etc. a budget should be established to,, enable implementation. Research is needed to establish optimum treatment strategies specifically for respiratory patients.
Keywords: chronic obstructive pulmonary disease; guidelines; respiratory patients; smoking cessation; OBSTRUCTIVE PULMONARY-DISEASE; SUSTAINED-RELEASE BUPROPION; GENERAL-POPULATION SAMPLE; RECEPTOR PARTIAL AGONIST; CIGARETTE-SMOKING; CONTROLLED-TRIAL; LUNG-FUNCTION; NICOTINE DEPENDENCE; CARBON-MONOXIDE; DOUBLE-BLIND